Experimental study on steam gasification of torrefied woodchips in a bubbling fluidized bed reactor. (1st July 2020) - Nguyen, Nhut M.; Alobaid, Falah; May, Jan; Peters, Jens; Epple, Bernd
Abstract: Biomass-based fuel is a potential renewable energy source despite its low energy density, high moisture content, and complex ash components due to its carbon-neutral nature. Torrefaction process, a promising biomass pretreatment method for upgrading biomass properties, is effective to generate fuel with higher calorific value and energy density. Torrefied biomass performs higher energy density and improved grindability characteristics as well as lower ratios of O/C and H/C compared to its raw source. This study presents an evaluation of the hydrogen production from steam gasification using torrefied woodchips as a feedstock in a pilot-scale bubbling fluidized bed reactor. The feedstock used is torrefied woodchips, which were treated at 250 °C in the N2 atmosphere. The experiments were conducted under isothermal and negative gauge pressure conditions in a pilot-scale bubbling fluidized bed reactor at different operating conditions such as gasification temperatures, steam-to-biomass ratio (SBR), and equivalence ratio (ER). Experimental results show that the high temperature and SBR are more favorable for hydrogen production and improve carbon conversion efficiency, while higher ER lowered content and yield of hydrogen. The optimal value of the steam-to-biomass ratio at 850 °C is 1.2 with the hydrogen content of 48.41% and the hydrogen yield of 0.039 Nm 3 /h. Highlights: Steam gasification experiments carried out for torrefied woodchips using bubbling bed reactor. Higher gasification temperatures result in hydrogen-enriched product gas. The content and yield of H2 in the product gas are proportional to steam-to-biomass ratio. The equivalence ratio considerably affects the composition of the product gas.